Frequency and effects of mutations in the KRAS gene on the survival of patients after surgical treatment of intrahepatic cholangiocarcinoma - B. N. Gurmikov; D. V. Kalinin; I. G. Nikitin; T. A. Zhinzhilo; A. N. Shipilova; A. V. Chzhao (Кубанский научный медицинский вестник, 2020)
Aim. To study the effect of mutations in the KRAS gene on the clinical course of intrahepatic cholangiocellular cancer (ICC) after surgical treatment in the Russian population.Materials and methods. A molecular genetic study of tumour tissue samples from 33 patients with intrahepatic cholangiocellular cancer obtained after surgical treatment was carried out using real-time polymerase chain reaction.Results. In the Russian population, the frequency of mutations in the KRAS gene in ICC was 27%, mainly in 12 (78%), 13 (33%), 61 (55%), 117 (44%) and 146 (44%) codons of 2, 3, 4 exons. In terms of KRAS gene mutations, intrahepatic cholangiocellular cancer is characterised by a pronounced heterogeneity. As a rule, the KRAS gene demonstrates multiple mutations at several loci and co-mutations in other genes, in particular, in IDH1/IDH2, PIK3CA, NRAS and BRAF genes. KRAS gene mutations in ICC were found to be significantly more common in women. The overall survival rate was significantly higher in patients with a KRAS mutation as compared to those with the wild type of the gene. Regarding the relapse-free survival rate in the groups of patients with the mutant and wild type of the KRAS gene, no significant differences were found.Conclusion. In the Russian population, no negative association between mutations in the KRAS gene and clinical outcomes was observed.